58‐4: Distinguished Student Paper: Active Matrix Field Sequential Color Electrically Suppressed Helix Ferroelectric Liquid Crystal for High Resolution Displays. Issue 1 (30th May 2018) - Shi, Liangyu; Srivastava, Abhishek Kumar; Cheung, Alex; Ho, Tsz Kin; Hsieh, Chia-Ting; Hung, Ching-Lang; Lin, Ching-Hsiang; Lin, Ching-Huan; Sugiura, Norio; Kuo, Chia-Wei; Chigrinov, Vladimir. G.; Kwok, Hoi Sing
Abstract : In this article, we disclose a 3‐inch 250ppi active matrix field sequential color electrically suppressed ferroelectric liquid crystal (ESHFLC) display. ESHFLC's ultra‐fast response time (~10µs at 6.67V/µm) enables the display resolution to be tripled via field sequential color technique. Photo‐alignment technology provides ESHFLC with optimal anchoring energy which contributes to a high contrast ratio over 10K:1. Specific 3T1C pixel circuit is designed to convert the analog signal to pulse width modulation. Thus the field sequential color ESHFLC display is achieved on LTPS TFT panel. With the delivered prototype, we successfully demonstrate the active matrix FSC ESHFLC integrated display system. We believe this display may replace IPS or FFS in the near future for portable mobile market. Moreover, high resolution FSC ESHFLC can find more applications in emerging virtual reality displays.